Nilai Eigen dan Vektor Eigen Universal Matriks Interval Atas Aljabar Max-Plus - Fitri Aryani; Tri Novita Sari (UIN Sultan Syarif Kasim Riau, 2016)
Discussion of eigenvalue dan eigenvector of a matrix has much to do. Matrix entries can be thereal, complex, fuzzy, and interval. This paper discusses the eigenvelue and eigenvector of interval matrixover max-plus algebra. An interval matriks has universal eigenvalue and eigenvector. Universaleigenvalue of an interval matrix is the eigenvalue of each The universal eigenvector can be foundby solving two-sided systems. For the eigenvalue is equal to 0 can use two-sided system with and for all While the eigenvalue not equal to 0 can use two-sidedsystem with and for all .Keywords: eigenvalue and eigenvector, eigenvalue and universal eigenvector, interval matrix, Max-plusalgebra.